Helminth community structure of the oven frog Leptodactylus latinasus (Anura, Leptodactylidae) from Corrientes, Argentina - Hamann, Mónika Inés (2006)
A total of 36 adult individuals of Leptodactylus latinasus were collected near the city of Corrientes, Province of Corrientes in Argentina. The main goals of this study were: (1) to determine the helminth parasite fauna of L. latinasus; (2) to determine the richness and diversity of parasites at the component and infracommunity levels; (3) to analyze the relationships between helminth, frog body size and sex; and (4) to identify and examine species affinity of helminth communities. The helminth component community of this frog's population consisted of 17 species. The predominant groups of parasites were the trematodes (adults: Glypthelmins repandum, Catadiscus inopinatus and Haematoloechus longiplexus; larvae: Travtrema aff. stenocotyle, Bursotrema aff. tetracotyloides, Styphlodora sp., unknown opisthogonimid species, Petasiger sp. and unknown strigeid species), followed by the nematodes (Cosmocerca podicipinus, C. parva, C. rara, C. cruzi, Schrankiana schranki and Aplectana hylambatis); other groups of parasites were represented by only one species (unknown larval cestode species and Centrorhynchus sp.). All parasite helminth species showed an aggregated pattern of distribution. The most infected organs were kidneys, small intestine, large intestine and pharyngeal zone. The host body size was important in determining the parasites abundance of G. repandum. At the level of component community G. repandum was the species with highest prevalence of infection and Bursotrema aff. tetracotyloides was the dominant species. Helminth species showed four significant pairs of covariation and two significant pairs of association in the infracommunities of Leptodactylus latinasus. © 2006 W. Stefański Institute of Parasitology, PAS.